The effectiveness of fast breaks in high-level basketball - Gerani, H.; Mexas, K.; Garefis, A.; Tsitskaris, G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Fast Break (F.B) is the quick offensive move from defense to offense in order to score an easy basket before the opponents being organised in defense1. Due to many coaches, F.B. is one of the most important elements in basketball because it creates many opportunities for high percentage shots2. The purpose of the present study was to evaluate the effectiveness of F.B.s in isolation and in relation to some variables (initiation, shooting area, fast break situation) in high-level basketball. Methods The sample consisted of 50 high-level basketball games (25 Men's National Teams games from the European Championship in 2001 and 25 games from the First Division of Greek National League in 2001-2002). The scouting software for individual and team sports called SportScout was used for the analysis of the situations. The chi square test (p < 0.05) was used for statistical analysis. Results The results revealed that significant differences (x2 = 1088,40, p<0.05) were found in the effectiveness of the F.B.s while 63% of the F.B. led to a basket, 9% led to an earned foul as the F.B. developed, 19% led to a missed shot and 9% led to an error. Considering the initiation, 56% of the F.B.s began from a defensive rebound and 41% from a stolen ball (x2 =794,849, p<0.05). Most of the F.B. (82%) ended up in the 3?? area and 82% of these resulted in a basket. 11,5% of the F.B.s ended up in the 3 point area, 45,1% resulting in score, and 6,5% ended up in the 2 point area with a 59,2% score rate (x2 =756,373 p<0.05). The most common F.B. situations were the 4 on 3 (13,6%), 1 on 1 (13,2%), 1 on 0 (11,6%), 3 on 2 (10,9%) and the 3 on 3 (10,4%)(x2 =216,367 p<0.05). The most effective situations were: 1 on 0 (90,9%), 4 on 2 (80%), 3 on 1 (79,4%), 3 on 2 (75,3%), 1 on 1 (73,5%) and 2 on 1 (73,2%) (x2 =35,163 p<0.05). Discussion/ Conclusions The present study concluded that F.B.s are highly effective in terms of scoring and most of them begin from a rebound or a stolen ball. Furthermore, the 3¨ area is the most preferable zone and has the highest success rates.